CT Angiographic Evaluation of Superior Gluteal Artery Branches in Lateral Sacroiliac Joint Fusion: A Pilot Study to Inform Preoperative Surgical Planning and Anatomic Parameters - Mallard CJ; Harned ME; Grider JS (Journal of Pain Research, 2025)
Christopher J Mallard, Michael E Harned, Jay S Grider Department of Anesthesiology, University of Kentucky, Lexington, KY, USACorrespondence: Christopher J Mallard, University of Kentucky, 2400 Greatstone Point Suite A-100, Lexington, 40504, KY, USA, Email cjmallard@uky.eduIntroduction: The sacroiliac (SI) joint can be a source of low back pain. Surgical techniques for fusion include lateral transiliac, posterolateral, sacro-alar iliac and posterior interpositional fixations. Although these various trajectories are supported by the literature, the lateral transiliac approach is the most extensively studied. However, this technique has been associated with concern for potential injury to branches of the superior gluteal artery (SGA). Currently, no preoperative workup includes the evaluation of SGA and its branches for location and potential injury during lateral fusion. We propose a clinical pathway for the identification and risk stratification of SGA injuries using preoperative CT of the pelvic vasculature and measurements of the proposed transiliac screw sites.Purpose: To determine whether preprocedural CT angiography (CTA) can identify the course of the SGA and its branches in relation to planned lateral transiliac SI joint fusion trajectories, thereby informing surgical planning and potentially reducing vascular risk.Patients and Methods: Twenty patients underwent preoperative CTA. Angiographic images were processed to generate a 3D vascular reconstruction. The proposed screw locations were identified, measured, and analyzed using descriptive statistics.Results: 20 patients’ images were analyzed with the average distance to the nearest SGA branch on the right being 19.0 mm ± 9.4 mm (minimum distance 5.75mm) and 17.3 mm ± 7.9 mm (minimum distance 5.97mm) on the left. Screw placement was altered in 1 of the 10 patients with an average total estimated blood loss (EBL) of 6.5mL ± 2.4mL in surgical patients.Conclusion: This pilot study suggests that preoperative CTA may aid proceduralists in planning lateral transiliac sacroiliac joint fusion by identifying the course of the SGA and its branches, potentially reducing the risk of vascular injury.Keywords: superior gluteal artery, sacroiliac joint fusion, lateral transiliac, sacroiliac joint, minimally invasive spine surgery, sacroiliitis